Sentinel surveillance for bacterial pneumonia and meningitis in children under the age of 5 in a tertiary pediatric hospital in Colombia - 2016 - Germán Camacho-Moreno; Carolina Duarte; Diego García; Viviana Calderón; Luz Yanet Maldonado; Liliana Castellar; Jaime Moreno; Jacqueline Palacios; Ángela Gallego; Orlando Castillo; Olga Sanabria; Ivy Talavera; et al. (Biomédica: revista del Instituto Nacional de Salud, 2021)
Introduction: Bacterial pneumonia and meningitis are vaccine-preventable diseases. Sentinel surveillance provides relevant information about their behavior. Objective: To present the data from sentinel surveillance carried out at the Fundación HOMI, Fundación Hospital Pediátrico La Misericordia in 2016. Materials and methods: We conducted a descriptive study from January 1 to December 31, 2016, on the daily surveillance of patients under 5 years of age diagnosed with pneumonia or bacterial meningitis according to PAHO’s definitions. We identified the microorganisms using the automated VITEKTM 2 system. Bacterial isolates were sent to the Microbiology Group at the Colombian Instituto Nacional de Salud for confirmation, serotyping, phenotypic, and genotypic characterization. Antimicrobial susceptibility profiles were established. Results: From 1,343 suspected cases of bacterial pneumonia, 654 (48.7%) were probable, 84% had complete Hib vaccination schedules, and 87% had complete pneumococcal vaccination schedules for age. Blood culture was taken in 619 (94.6%) and 41 (6.6%) were positive while S. pneumoniae was isolated in 17 (41%) of them. The most frequent serotype was 19A in five cases (29.4%), and four 19A serotypes were associated with the reference isolate ST320. The incidence rate of probable bacterial pneumonia was 7.3 cases/100 hospitalized patients, and lethality was 2.1%. As for bacterial meningitis, 22 suspected cases were reported, 12 (54%) were probable, four (33%) were confirmed: two by Escherichia coli and two by group C N. meningitidis. The incidence of probable bacterial meningitis was 0.14 cases/100 hospitalized patients. Conclusion: Streptococcus pneumoniae serotypes 19A and 3 were the most frequent cause of pneumonia. Spn19A is related to the multi-resistant clone ST320. Strengthening and continuing this strategy will allow understanding the impact of vaccination.